Hydrogen Peroxide Involved in Tip Growth of Wheat (TriticumAestivum) Root Hairs by High Concentration Chlorogenic Acid - juan, Jing Hong-; jie, Yi Yan-; qiang, Zhang Guo- (Canadian Journal of Agriculture and Crops, 2017)
In order to clarify effects and mechanism of chlorogenic acid (CA) on the early development of six-day wheat seedlings, root growth were detected in the paper. Results have showed that moderate CA promoted the growth of root whereas high concentration CA inhibited the growth of root. In order to elaborate the mechanism of suppressive growth of root by high concentration CA, contents of hydrogen peroxide (H2O2) and superoxide anion (O2-.) in roots of wheat seedlings were measured. CA both decreased the contents of H2O2 and O2-.. In addition, exogenous H2O2 could recover the repressive growth of primary root. Furthermore, CA markedly increased the activity of NADPH oxidases and significantly promoted Peroxidase (POD) activity to increase the scavenging ability of H2O2. Therefore, inhibitory growth of primary roots and root hairs by CA potentially attributed to decrease of H2O2 which was eliminated by POD at root tips of wheat seedlings.